Electrochemically reduced graphene oxide integrated with carboxylated-8-carboxamidoquinoline: A platform for highly sensitive voltammetric detection of Zn(II) ion by screen-printed carbon electrode - Ling Ling Tan; Nur Syamimi Mohamad; Nurul Izzaty Hassan; Choo Ta Goh (PLoS ONE, 2025)
Zinc has been demonstrated to boost immune response during SAR-CoV-2 infection, where it prevents coronavirus multiplication. Clinical investigations have testified to its beneficial effects on respiratory health and its deficiency may reduce immune function. A highly sensitive detection of Zn(II) ion via differential pulse voltammetry (DPV) utilizing an environmentally friendly modified screen-printed carbon electrode (SPCE) of electrochemically reduced graphene oxide (ErGO) embedded with carboxylated-8-carboxamidoquinoline (CACQ) as Zn(II) chelating ligand. The green CACQ/ErGO-modified SPCE was characterized by spectroscopy techniques, such as Fourier-transform infrared (FTIR) spectroscopy, Raman spectroscopy, and field-emission scanning electron microscopy with energy dispersive X-ray (FESEM-EDX). The modified electrode-solution interface was studied by electrochemical cyclic voltammetry (CV) and DPV methods. The CACQ-modified wrinkled ErGO electrode conferred a large surface-to-volume ratio with multiple binding sites resulting in greater opportunity for multiple dative covalent binding events with Zn(II) via coordination chemistry, and considerably accelerated the electron transfer rate at the electrode surface. The green Zn(II) sensor demonstrated a quick response time (60 s), broad linear range [1 pM-1 μM Zn(II) ion], a limit of detection (LOD) of 0.53 pM, 35 days of storage period (≥80% of its initial response retained), good reproducibility [relative standard deviation (RSD) = 3.4%], and repeatability (RSD = 4.4%). The developed electrode was applied to determine Zn(II) ion concentration in dietary supplement samples, and the results were in good agreement with those obtained from inductively coupled plasma-mass spectrometry (ICP-MS).